PENGARUH ALAT PERAGA TERHADAP KEMAMPUAN BERHITUNG PERMULAAN ANAK USIA 5-6 TAHUN - Ghina Aulia; Isti Rusdiyani; Ratih Kusumawardani; Dian Surya Apriliyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low initial numeracy ability of children aged 5-6 years at Aisyiyah Bustanul Athfal Pandeglang Kindergarten due to the mathematics learning method that tends to be monotonous and abstract. This study aims to determine the effect of the use of addition circuit teaching aids on children's summation calculation ability. The theoretical foundation refers to Jean Piaget's theory of concrete pre-operational stages, Susanto's concept of initial calculation, and the function of Sudjana props. The research method uses quantitative quasi-experimental experiments with a nonequivalent control group design. The samples were divided into class B1 as an experimental group (using a summing circuit) and class B2 as a control group (conventional method). Data collection uses performance assessment instruments that have been tested for validity and reliability. SPSS 22-assisted data analysis includes paired sample t-test and independent sample t-test. The results of the paired sample t-test of the experimental class showed an increase in the average score from 33.20 to 43.27 with a difference of 10.067 and Sig. 0.000. While the control class was only 6,333 apart. The results of the independent sample t-test obtained a Sig. (2-tailed) value of 0.002 (< 0.05), proving that there was a significant difference in final achievement between the two groups. It was concluded that the use of summation circuit teaching aids had a significant effect and was much more effective in improving children's initial numeracy skills. Keywords: Addition Circuit Teaching Aids, Counting Starting, Cognitive.